Pubblicato il

Scarica l’esercizio numero 33 pagina 518 (Matematica 3 nuova edizione)

testo

\( \int{e^{-x+2}e^xdx}\)

Ricordando che:

\(a^n*a^m=a^{n+m}\)

Si ha:

\(\int{e^{(-x+2)+(x)}dx}\)

\(\int{e^{\cancel{-x+2+x dx}}} \)

\(\int{e^2}dx\)

Ricordando che:

\(\int{ \alpha f(x)}dx= \alpha \int{f(x)}dx\)

Rimane:

\(e^2\int{1dx}\)

\(e^2\int{x^0dx}\)

Ricordando che:

\(\int{x^{\alpha}dx=\frac{x{\alpha+1}}{\alpha+1}+c}\)

vale per \( \alpha \neq-1\)

Si ha:

\(e^2*(\frac{x}{1})+c\)

Quindi:

\(\int{e^{-x+2}e^xdx=e^2x+c}\)